2019
DOI: 10.1186/s12887-019-1616-2
|View full text |Cite
|
Sign up to set email alerts
|

Trends, determinants, and newborn mortality related to thermal care and umbilical cord care practices in South Asia

Abstract: Background Although child mortality has decreased over the last several decades, neonatal mortality has declined less substantially. In South Asia, neonatal deaths account for the majority of all under-five deaths, calling for further study on newborn care practices. We assessed five key practices: immediate drying and wrapping, delayed bathing, immediate skin-to-skin contact after birth, cutting the umbilical cord with a clean instrument, and substances placed on the cord. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
3
20
0
1
Order By: Relevance
“…Also, mothers who had attended ANC visits had increased odds of having SSC with their newborns immediately after delivery, compared with those who had no ANC visits. Similar findings have been reported in other studies [ 17 , 35 ]. ANC is an avenue to educate, counsel and prepare pregnant women for delivery.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, mothers who had attended ANC visits had increased odds of having SSC with their newborns immediately after delivery, compared with those who had no ANC visits. Similar findings have been reported in other studies [ 17 , 35 ]. ANC is an avenue to educate, counsel and prepare pregnant women for delivery.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the findings from previous studies which showed that the practice of SSC between the mother and the newborn was significantly more common in health facility based delivery compared with home births [ 32 , 33 ]. Skilled birth attendants at health facilities may be more knowledgeable about SSC than traditional birth attendants, making it more likely to be practiced in hospital deliveries [ 34 , 35 ]. Furthermore, the mode of delivery was significantly associated with SSC between mothers and their newborn immediately after birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However higher prevalence of skin to skin care was reported from south Asian countries. In Bangladesh and Nepal about 25% and 38% of women reported practicing skin to skin care of newborns respectively [16]. Studied women do not believe that skin to skin care is helpful to keep newborn warm.…”
Section: Discussionmentioning
confidence: 99%
“…of newborns in Nepal receive immediate drying and wrapping [16]. In current study area, commonly drying and wrapping are done after newborn bath except in the circumstance of health facility delivery, where limited access to water and/or health workers' advice might have hindered early newborn bath.…”
Section: Discussionmentioning
confidence: 99%